2001
DOI: 10.1897/1551-5028(2001)020<0597:eoccev>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF CHRONIC Cd EXPOSURE VIA THE DIET OR WATER ON INTERNAL ORGAN-SPECIFIC DISTRIBUTION AND SUBSEQUENT GILL Cd UPTAKE KINETICS IN JUVENILE RAINBOW TROUT (ONCORHYNCHUS MYKISS)

Abstract: New regulatory approaches to metal toxicity (e.g., biotic ligand model [BLM]) focus on gill metal binding and tissue-specific accumulation of waterborne metals; the dietary route of exposure and dietary/waterborne interactions are not considered, nor are the consequences of chronic exposure by either route. Therefore, we studied the effect of the same gill Cd load (approximately 2.5 microg/g), achieved by a chronic, 30-d exposure to Cd either via the diet (1,500 mg/kg) or the water (2 microg/L), on tissue-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 16 publications
8
30
3
Order By: Relevance
“…Taylor et al (2003) also reported no significant differences in log K Cu in hard water as well as in soft water between the same two species, although they observed significantly greater binding capacity for Cu in YP relative to RBT in both hard and soft water. The log K Cd value in RBT of the present study (7.34) was in reasonable agreement with those (7.60 and 7.05) reported earlier by Hollis et al (1999) and Szebedinszky et al (2001), respectively, in RBT in moderately hard water. However, the value in this study is much less than the value (8.60) reported by Playle et al (1993aPlayle et al ( , 1993b in fathead minnow, which translates to a more than 20-fold greater affinity of fathead minnow gills for Cd compared with RBT.…”
Section: Short-term (3-h) Gill CD and Ca Binding In Laboratoryreared supporting
confidence: 93%
“…Taylor et al (2003) also reported no significant differences in log K Cu in hard water as well as in soft water between the same two species, although they observed significantly greater binding capacity for Cu in YP relative to RBT in both hard and soft water. The log K Cd value in RBT of the present study (7.34) was in reasonable agreement with those (7.60 and 7.05) reported earlier by Hollis et al (1999) and Szebedinszky et al (2001), respectively, in RBT in moderately hard water. However, the value in this study is much less than the value (8.60) reported by Playle et al (1993aPlayle et al ( , 1993b in fathead minnow, which translates to a more than 20-fold greater affinity of fathead minnow gills for Cd compared with RBT.…”
Section: Short-term (3-h) Gill CD and Ca Binding In Laboratoryreared supporting
confidence: 93%
“…In the equivalent Cd treatments, Cd concentration in gills was lower than in other tissues except for the muscle. Szebedinszky et al (2001) reported that gills are important in taking up dissolved Cd across the apical cell membranes, and resulted in the highest branchial Cd concentration in the waterborne Cd exposed fish, but in dietborne Cd exposed fish, the Cd in gills was probably transferred from the bloodstream across the basolateral cell membranes. The difference of transport mechanism led to lower gill Cd concentration in fish exposed to dietbrone that those exposed to waterborne Cd (Dang and Wang, 2009).…”
Section: Cadmium Iron and Calcium Accumulations In Different Tissuesmentioning
confidence: 99%
“…For example, Weston et al (2000) concluded that the principal route of metals bioaccumulation for deposit-feeding organisms is ingestion of contaminated sediment, desorption of metals in the gut, and absorption across the gut wall. However, although the gill is not a primary target for dietary metal accumulation, dietary metals such as Cu (Handy 1992;Miller et al 1993;Kamunde et al 2001Kamunde et al , 2002b and Cd (Szebedinszky et al 2001) can sometimes accumulate in fish gills. Concentrations of Cu accumulated from dietary sources may exceed those associated with toxicity during waterborne exposures (MacRae et al 1999), possibly because metal accumulated via diet (from blood) is protein bound by the time it reaches the gill and therefore is not toxic.…”
Section: Risk Assessments Of Inorganic Metals and Metalloidsmentioning
confidence: 99%
“…In some cases dietary exposures including ingestion of particles can be predominant, water only bioassays can be misleading (Farag et al 1994(Farag et al , 1999Lee et al 2000a, b;Fisher 2001b, 2002;Szebedinszky et al 2001;Hare et al 2003). Unique potential exposure pathways such as biofilm in rivers (Clements 2002) must be considered.…”
Section: Risk Assessments Of Inorganic Metals and Metalloidsmentioning
confidence: 99%